Diksyunaryong panghanapbuhay. - Philippines. Komisyon sa Wikang Filipino (Pasig, Metro Manila Komisyon sa Wikang Filipino, 1993)
English-Tagalog dictionary of industrial terminology.
English and Tagalog.
Keywords: Industries -- Dictionaries; Technology -- Dictionaries; English language -- Dictionaries -- Tagalog